Benford's law: Planning and analysis of the planned values in the defense budget - Đorić Igor; Ranisavljević Mihajlo; Kocka Đole (Trendovi u Poslovanju)
In the age of a large number of data that scale up on a daily basis, what becomes highly relevant is the credibility analysis and accuracy, i.e., detecting potential manipulations of the respective data. Benford's law is widely used to detect anomalies in sets of data, ranging from official population numbers, stock prices and information in scientific papers to financial reports in companies' financial statements taking the form of forensic accounting. Benford's law as a tool to analyze data in this paper focuses on the planned values expressed in the budget of the defense system in the Republic of Serbia. Research in this sphere of social life is important from the viewpoint of accurately presenting the activities and of transparency of future actions, of minimizing misuses and, henceforth, increasing trust in the operation of institutions. This paper identifies a minimal discrepancy in publicly available data in the laws on budget for the observed period, which suggests a proper distribution of assets approved for funding the defense system.